(untitled) (Media Kesehatan Masyarakat Indonesia, 2019)
The prevalence of dysmenorrhea is mostly experienced by teenagers. Study showed that woman who did exercise had less proportion to feel dysmenorrhea. For that reason, this research purpose to analyze effect exercise on primary dysmenorrhea among student grade 10th in SMA Negeri 78 Jakarta Barat, which family historical menstruation pain, menstruation period, menarche, stress, coffee consumption, smoke exposure, and alcohol consumption was controlled. To reach that purpose, the research used analysis method with case control study. The minimum sample size used in this case-control study was calculated based on the hypothesis testing of different proportions so that we obtained a total sample of cases and controls of 84 female students. Bivariate analysis showed alcohol consumption and exercise had related to primary dysmenorrhea (p-value < 0.05). After controlled some variables, multivariate analysis showed exercise had effected to primary dysmenorrhea with p-value 0.043 and OR 1.937 (95% CI: 1.124 – 3.913). The result showed lack of exercise had a chance 1.937 times to feel primary dysmenorrhea.